Multicenter, single‐arm, phase II study of the continuous use of panitumumab in combination with FOLFIRI after FOLFOX for RAS wild‐type metastatic colorectal cancer: Exploratory sequential examination of acquired mutations in circulating cell‐free DNA. Issue 12 (5th July 2022) - Watanabe, Jun; Maeda, Hiromichi; Nagasaka, Takeshi; Yokota, Mitsuru; Hirata, Keiji; Akazawa, Naoya; Kagawa, Yoshinori; Yamada, Takeshi; Shiozawa, Manabu; Ando, Takayuki; Kato, Takeshi; Mishima, Hideyuki; et al.
Abstract: This multicenter single‐arm, phase II study evaluated the efficacy and safety of uninterrupted panitumumab usage combined with cytotoxic doublets for unresectable/metastatic colorectal cancer (mCRC). Additionally, clinical value of the RAS/BRAF mutation status in circulating cell‐free DNA (ccfDNA) was evaluated; this evaluation was measured independently of the protocol treatment. Eligible patients with RAS wild‐type mCRC who had received the first‐line panitumumab plus FOLFOX treatment were recruited and administered continuous panitumumab combined with FOLFIRI. Progression‐free survival (PFS) at 6 months was the primary endpoint, with threshold and expected values of 35% and 50%, respectively. In total, 54 patients were enrolled between October 2017 and October 2019. The crude 6‐month PFS rate was 37.0%, with a 4.8‐month median PFS. The response rate and disease control rate were 16.7% and 50.0%, respectively. Notably, of the 54 participants, 17 showed RAS / BRA F mutations until the end of the protocol treatment and of the 22 patients with progressive disease as their best response, 10 possessed RAS / BRAF mutations in their plasma ccfDNA at baseline. The median PFS significantly differed among patients harboring tumors with BRAF and RAS mutations and those with wild‐type tumors. In conclusion, our study failed to show the expected efficacy of the continuous panitumumab use in the second‐line treatment. Liquid biopsy discriminated the duration of PFS according to the mutation status. The effectiveness of continuous treatment with panitumumab should be evaluated in patients with RAS/BRAF wild‐type mCRC determined by liquid biopsy at the start of the second‐line treatment. Abstract : What's new? Epidermal growth factor receptor (EGFR) inhibitors are valuable in the treatment of metastatic colorectal cancer (mCRC), and their continuous use, across both first‐ and second‐line treatment for mCRC, is an appealing therapeutic strategy. Little is known, however, about the efficacy of continuous anti‐EGFR therapy. Here, continuous use of the anti‐EGFR antibody panitumumab, from first‐line FOLOX to second‐line FOLFIRI treatment, failed to reach expected clinical efficacy for progression‐free survival among patients with RAS wild‐type mCRC. Prognosis was improved, however, for patients with wild‐type RAS/BRAF. The findings suggest that continuous panitumumab treatment is beneficial in select mCRC patients, warranting further investigation.